2006
DOI: 10.1208/pt070373
|View full text |Cite
|
Sign up to set email alerts
|

Influence of long-term stability conditions on microbicidal nucleoside prodrug (WHI-07)-loaded gel-microemulsion

Abstract: The objective of this study was to evaluate the long-term stability of the antiretroviral spermicide WHI-07 (5-bromo-6-methoxy-5,6-dihydro-3′-azidothymidine-5′-(p-bromophenyl)-methoxyalaninyl phosphate) in a polymer-based microemulsion. The recovery and stability of WHI-07 in gelmicroemulsion was examined by a validated high-performance liquid chromatography (HPLC) method. The stability was examined over a period of 24 weeks at 3 controlled temperatures (4ºC, 25ºC, and 40ºC). The recovery of the prodrug from 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Microemulsions can deliver larger amounts of topically applied WHI-07 and VDDTC into the vaginal mucosa than traditional vehicles because of their capacity for enhanced solubilization and greater bioavailability (Tenjarla, 1999). The microemulsion-based system composed (w/w) of Phospholipon 90G (5.1%) and Captex 300 (10.8%) as the oil phase with Cremophor EL (7.6%) as surfactant, propylene glycol (4.2%) and polyethylene glycol 200 (4.2%) as cosurfactants, and water (66.1%) as a carrier and a preservative (0.2% sodium benzoate) (D'Cruz and Uckun, 2006). Polymer suspensions of SeaSpen PF (0.9%) and Viscarin GP-209 (0.9%) carrageenans were selected as additives to the microemulsion to obtain a gel with desirable viscosity containing WHI-07 and VDDTC with thickening capability and compatibility with vaginal mucosa.…”
Section: Gel-microemulsion Formulation Of Whi-07 Plus Vddtcmentioning
confidence: 99%
“…Microemulsions can deliver larger amounts of topically applied WHI-07 and VDDTC into the vaginal mucosa than traditional vehicles because of their capacity for enhanced solubilization and greater bioavailability (Tenjarla, 1999). The microemulsion-based system composed (w/w) of Phospholipon 90G (5.1%) and Captex 300 (10.8%) as the oil phase with Cremophor EL (7.6%) as surfactant, propylene glycol (4.2%) and polyethylene glycol 200 (4.2%) as cosurfactants, and water (66.1%) as a carrier and a preservative (0.2% sodium benzoate) (D'Cruz and Uckun, 2006). Polymer suspensions of SeaSpen PF (0.9%) and Viscarin GP-209 (0.9%) carrageenans were selected as additives to the microemulsion to obtain a gel with desirable viscosity containing WHI-07 and VDDTC with thickening capability and compatibility with vaginal mucosa.…”
Section: Gel-microemulsion Formulation Of Whi-07 Plus Vddtcmentioning
confidence: 99%
“…WHI-07 was solubilized in a lipophilic sub-micron (30-80 nm) particle size microemulsion using selected pharmaceutical excipients identified through systemic mapping of ternary phase diagrams and drug solubilization studies (D'Cruz and Uckun, 2001a). The microemulsion-based system was composed (w/w) of Phospholipon 90G (5.1%) and Captex 300 (10.8%) as the oil phase with Cremophor EL (7.6%) as surfactant, propylene glycol (4.2%) and polyethylene glycol 200 (4.2%) as cosurfactants, and water (66.1%) as a carrier and a preservative (0.2% sodium benzoate) (D'Cruz and Uckun, 2006). Polymer suspensions of SeaSpen PF (0.9%) and Viscarin GP-209 (0.9%) carrageenans were selected as additives to the microemulsion to obtain a gel with desirable viscosity containing 2.0% WHI-07 with thickening capability and compatibility with vaginal mucosa (D'Cruz and Uckun, 2001a).…”
Section: Gel-microemulsion Formulation Of Whi-07mentioning
confidence: 99%
“…The highest concentration of WHI-07 chosen for the porcine mucosal irritation study was based on the lack of local, systemic and reproductive toxicity observed in two 13-week subchronic studies in CD1 and B6C3F1 mice (D'Cruz et al, 2000;Uckun, 2001b, 2001c), a 14-day developmental toxicity study in NZW rabbits , and a 2-year carcinogenicity study in B6C3F1 mice . A 6month stability of 2% WHI-07-loaded gel-microemulsion revealed that the prodrug was stable in microemulsionbased formulation (D'Cruz and Uckun 2006).…”
Section: Gel-microemulsion Formulation Of Whi-07mentioning
confidence: 99%
“…Microemulsions have emerged as novel vehicles for drug delivery for its advantage of spontaneous formation, ease of manufacturing and scale-up, thermodynamic stability, improved drug solubility of hydrophobic drugs and bioavailability [4] . D'Cruz developed gel microemulsions GM 4 and GM 144 as vaginal spermicides and intravaginal drug delivery vehicles to prevent the HIV and other sexually transmitted diseases [5,6]. Here we prepared microemulsion to load Nifeviroc in order to improve the water solubility and studied the stability of the Nifeviroc-MEs of different load capacity (0.1%, 0.2%, 0.3%) in order to set base for the use of microbicides.…”
Section: Introductionmentioning
confidence: 99%